Applicazione dei sistemi GIS nel verde urbano - L'esperienza della cittí di Torino - Davide Giuseppe Ture (mediaGEO soc. coop., 2018)
The City of Turin launched in 2015 a series of Space Analysis and recalculation of the area managed to public green space. The job was to select all the areolas that made up the garden / green area. Once the selection phase has been completed, the shapefile has been saved in a dedicated folder and coded one for each district garden, to perform the estimative metric calculation that quantifies the actual turf surface of the Garden itself and assigns its maintenance cost based on the type of processing. From 2017 a pilot project has been activated on the District 2 of the City of Turin that directly uses the attribute tables of QGIS for the importation of metadata on the WebMap.